Non‐Invasive Intracranial Pressure Monitoring with Transcranial Doppler in a Patient with Progressive Cerebral Venous Sinus Thrombosis. Issue 3 (10th December 2012) - Wakerley, Benjamin; Yohana, Kusuma; Luen Teoh, Hock; Tan, Clement W.; Chan, Bernard P.L.; Sharma, Vijay K.
ABSTRACT In many intracranial disease states, monitoring of intracranial pressure (ICP) is essential to evaluate response to the therapeutic measures as well as estimation of prognosis. Although, direct estimation of ICP is reliable, it is invasive and not possible in all patients. Transcranial Doppler (TCD) ultrasonography is a bedside and noninvasive technique that provides reliable and real‐time information about cerebral hemodynamics. We present a case of extensive and progressive cerebral venous sinus thrombosis in which TCD served as an excellent tool for monitoring ICP and the serial observations correlated closely with clinical status and ophthalmological findings.